Understanding Intimate Partner Violence: Why Coercive Control Requires a Social and Systemic Entrapment Framework - Tolmie, Julia; Smith, Rachel; Wilson, Denise (Violence Against Women, 2024)
How intimate partner violence (IPV) is conceptualized affects what we see when we look at situations involving IPV and what we think the solutions to the problem of IPV are—either in individual cases or in the development of broader legal and policy responses. In this article, it is suggested that while conceptualizing IPV as coercive control is an improvement over previous understandings, it does not go far enough. Coercive control must be located within a broader conceptualization of IPV as a form of social and systemic entrapment if it is not to operate in a harmful manner for victim-survivors.